Homecare workers in Italy: a narrative review - Simeone, S.; Vellone, E.; Pucciarelli, G.; Alvaro, R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. The progressive ageing and ever-increasing life expectancy of the world’s population are accompanied by an increase in chronic pathologies. Italy continues to be the nation with the highest percentage of senior citizens. Recent economic crises and movements of social change have led to a gradual increase in the use of homecare workers for the territorial and family management of chronic illnesses. Contrary to what has happened in other countries, in Italy an informal logic has prevailed regarding the recruitment and the employment of homecare workers, hindering the evolution of this sector. Aim. This narrative review focuses on the role of homecare workers, as it appears in Italian researches. Methods. A narrative review was conducted using the following electronic databases: CINAHL Complete, MEDLINE, MEDLINE Complete, PsycINFO, and SocINDEX. Only studies conducted in the past 20 years with an Italian Homecare Worker (HCW) target population were considered. Data were extracted from each manuscript to allow for quick comparisons of information, such as research objectives, study methodologies, data collection tools, and relative results. Two reviewers independently extracted the following data for each study: region, setting context, participant characteristics, group description and sample, outcomes measured, and a description of the main results. Results. From the analysis of heterogeneous Italian literature, the importance of homecare workers is clear. Their work not only influences assisted individuals but also informal caregivers and the direct costs of the Italian national health system. Conclusion. Homecare workers are important in Italian society. The little attention that the scientific literature has paid to this population may be due to the difficulty of finding subjects with a legal status and, therefore, who are willing to participate in specific investigations. Investigating the dyad of care and extending these investigations to the surrounding family context, seem to be the major priorities that should be explored by future research.